Wikipedia and archival problems: A Derridean impression - Dominic Pretorius (The Thinker)
As much as Archive Fever: A Freudian Impression is Jacques Derrida’s meditation on the notion of archives as it relates to Sigmund Freud, the person and the psychoanalytic tradition, many of his insights can be applied to theories of the archive in general. Moreover, he is particularly concerned with the meaning of archives at a moment of rapid technological development.